Pulmonary arterial hypertension in children with congenital heart disease: a deeper look into the role of endothelial progenitor cells and circulating endothelial cells to assess disease severity - Calderón-Colmenero, Juan; Massó, Felipe; González-Pacheco, Héctor; Sandoval, Julio; Guerrero, Carlos; Cervantes-Salazar, Jorge; García-Montes, José A.; Paéz, Araceli; Pereira-López, Gabriela I.; Zabal-Cerdeira, Carlos; Sandoval, Juan Pablo (Frontiers in Pediatrics, 2023)
Endothelial progenitor cells and circulating endothelial cells have been proposed as useful markers of severity and disease progression in certain vascular diseases, including pulmonary arterial hypertension. Our study focused on evaluating the levels of circulating endothelial progenitor cells and circulating endothelial cells in patients with congenital left-to-right shunts and pulmonary hypertension undergoing definitive repair. Endothelial progenitor cells (identified by simultaneous co-expression of CD45dim, CD34 + and KDR2 + surface antibodies) and circulating endothelial cells (identified by simultaneous co-expression of inherent antibodies CD45-, CD31+, CD146 + and CD105+) were prospectively measured in seventy-four children (including children with Down syndrome), median age six years (2.75–10), with clinically significant left-to-right shunts undergoing transcatheter or surgical repair and compared to thirty healthy controls. Endothelial progenitor cells and, particularly, circulating endothelial cells were significantly higher in children with heart disease and pulmonary arterial hypertension when compared to controls. Endothelial progenitor cells showed significant correlation with pulmonary vascular resistance index when measured both systemically (r = 0.259; p = 0.026) and in the superior vena cava (r = 0.302; p = 0.009). Children with Down syndrome showed a stronger correlation between systemic cellularity and pulmonary vascular resistance index (r = 0.829; p = 0.002). Endothelial progenitor cells were reduced along their transit through the lung, whereas circulating endothelial cells did not suffer any modification across the pulmonary circulation. In children with yet to be repaired left-to-right shunts, endothelial progenitor cells and circulating endothelial cell counts are increased compared to healthy subjects.